2022
DOI: 10.3390/ph15121565
|View full text |Cite
|
Sign up to set email alerts
|

Non-Apoptotic Programmed Cell Death in Thyroid Diseases

Abstract: Thyroid disorders are among the most common endocrinological conditions. As the prevalence of thyroid diseases increases annually, the exploration of thyroid disease mechanisms and the development of treatments are also gradually improving. With the gradual advancement of therapies, non-apoptotic programmed cell death (NAPCD) has immense potential in inflammatory and neoplastic diseases. Autophagy, pyroptosis, ferroptosis, and immunogenic cell death are all classical NAPCD. In this paper, we have compiled the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 174 publications
0
1
0
Order By: Relevance
“…26,27 As an essential dietary vitamin derived from fruits and vegetables, vitamin C can protect healthy cells from oxidative insults and function as a scavenger of free radicals in the body. 28 Vitamin C deficiency is a common feature of person living with obesity. 29 In agreement with previous study results, we found that person living with obesity had lower levels of vitamin C. 30 Part of the reason may be the decreased consumption of fruits and vegetables in obese individuals.…”
mentioning
confidence: 99%
“…26,27 As an essential dietary vitamin derived from fruits and vegetables, vitamin C can protect healthy cells from oxidative insults and function as a scavenger of free radicals in the body. 28 Vitamin C deficiency is a common feature of person living with obesity. 29 In agreement with previous study results, we found that person living with obesity had lower levels of vitamin C. 30 Part of the reason may be the decreased consumption of fruits and vegetables in obese individuals.…”
mentioning
confidence: 99%